Tablet image - Balozian, Puzant (2014)
The functionality and performance of technology has consistently predicted technology use. However, there are other reasons related to social and psychological forces influencing technology use. This study investigates the social drivers of tablet technology use. In particular, the study focuses on the image associated with tablet technology and the influence of this image on Tablet Use. Using a survey of 157 tablet users, the study discovers that tablet image is a driving force behind the use of some of the functions in tablets. The results suggest that designing tablet functions that are socially visible to the public cognition may be an important reason behind tablet adoption and use, on the backdrop of a Tablet Image. The results have theoretical implications for IT adoption theories and practical implications for the design and upgrade of the next generations of tablets.